PERBEDAAN KELELAHAN KERJA SATPAM ANTARA SHIFT PAGI, SHIFT SIANG DAN SHIFT MALAM DI PT. INDONESIA POWER UBP SEMARANG - Andika S. Manik; Siswi Jayanti; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Work fatigue can be defined as a protection mechanism of the body to avoid further damage so that recovery occurs after the break. Some factors from fatigue the caused by shift work, workload, and work environment. The purpose of this study was to describe, analyze workload and work fatigue difference at security staff between the morning, day and night shifts in PT. Indonesia Power UBP Semarang. Type of this study was a quantitative study with analysis of explanation or explanatory research. Design of this study was using cross sectional research. Population of this study is 48 security in PT. Indonesia Power UBP Semarang. Determination of sample was using simple random sampling method with a purposive sampling approach obtained 12 samples. Statistical test was using are non parametric anova test. Output of one way anova of hypothesis there is no difference of security workload between morning shift and day shift (p=0,846; α= 0,05), there is no difference of security workload between day shift and night shift (p=0,343; α= 0,05) and there is no difference of security workload between morning shift and night shift (p=0,710; α= 0,05). And there is a difference of security fatigue between morning shift and day shift (p=0,010; α= 0,05), there is no difference of security fatigue between day shift and night shift (p=0,153; α= 0,05) and there is a difference of security fatigue between morning shift and night shift (p=0,016; α= 0,05). Researcher recommend that company should be increasing the number of security.